Microsatellite genotypes of common voles, Microtus arvalis - Searle, Jeremy; Martínková, Natália; Barnett, Ross; Cucchi, Thomas; Struchen, Rahel; Pascal, Marine; Pascal, Michel; Fischer, Martin; Higham, Thomas; Brace, Selina; Ho, Simon; Quere, Jean-Pierre; et al. (Dryad Digital Repository, 2013)
Genotypes of 14 microsatellite loci in 24 populations of common voles in Arlequin format. Binned fragment size is given. Samples are labelled with isolate number.